Rapid method of quantification of tight‐junction organization using image analysis. Issue 2 (4th December 2012) - Terryn, Christine; Sellami, Mehdi; Fichel, Caroline; Diebold, Marie‐Danielle; Gangloff, Sophie; Le Naour, Richard; Polette, Myriam; Zahm, Jean‐Marie
Abstract: The spatial organization of proteins in a cell population or in tissues is an important parameter to study the functionality of biological specimens. In this article, we have focused on tight junctions which form network‐like features in immunofluorescence microscopy images. Usually, the organization or disorganization of tight junctions is noticed qualitatively. The aim of this article is to present a simple method to quantify the organization level of tight junction network using image analysis with a dedicated macro developed with Image J software. The method has been validated with simulated images displaying regular decrease of network organization. Then, the macro has been applied to immunofluorescence microscopy images of cells in culture and of tissue sections. © 2012 International Society for Advancement of Cytometry